Body language at work - Furnham, Adrian ([S.l.] : Chartered Institute of Personnel & Development, 1999)
"Body Language at Work" will transform your ability to interpret critical gestures and tell-tale expressions in yourself as well as others. Adrian Furnham, Professor of psychology, writer and broadcaster dispels the claims and common misconceptions surrounding body talk to reveal the true significance of this fascinating yet powerful form of communication. He covers: how we betray attitudes, emotions and personality in non-verbal ways - what body language can and can't communicate - the nature and meaning of signals - eye gaze, facial expression, gesture, posture, touch - what our clothes, jewellery and even choice of deodorant say about us - how far we can expose the artful dodger, the office phoney and the interview fake.